Responsabilidade social empresarial na indústria de calçados paulista: Uma análise dos pólos de franca e Birigui - Barbosa, Agnaldo de Sousa [UNESP]; Alves, Elvisney Aparecido; Filho, Hélio Braga (My University, 2012)
The footwear sector has characteristics that distinguish it in discussing the topic of corporate social responsibility, it is an industry whose production is based on technological bases typical of manufacturing and craftsmanship. Considering these peculiarities, the objective pursued here is a reflection based in the perception of the socially responsible behavior by entrepreneurs from Franca and Birigui, two major industrial clusters specialized in the production of footwear. The article is based on research conducted in both territories through interviews. In industrial cluster of Franca, it was found that most of the actors interviewed, associated with the Pro-Child Institute, does not recognize social responsibility as an obligation of the company, but as a moral issue. In industrial cluster of Birigui the corporate engagement is more effective, materializing especially in the association of most manufacturers in the Pro-Child Institute and in the attitude to assume social responsibility as an essential task of the business within the new reality of capitalism.
Corporate social responsibility in the footwear industry in São Paulo (Brazil): An analysis of the industrial clusters of franca and Birigui
Keywords: Corporate social responsibility; Footwear industry; Prochild institute